Mitigating jaw osteonecrosis: bioactive glass and pericardial membrane combination in a rat model - Pellicano, Alexandre Antonio; Benites, Bernar M.; Paschoa, Amanda F. N.; Oliveira, Laura C.; Campos, Ana Carolina P.; Martins, Daniel O.; Real, Caroline C.; de Paula Faria, Daniele; Fonseca, Felipe P.; Martinez, Raquel R. C.; Pagano, Rosana L.; Fregnani, Eduardo R. (Frontiers in Oncology, 2024)
Objectives: Bisphosphonates (BFs) show clinical effectiveness in managing osteoporosis and bone metastases but pose risks of bisphosphonate-related jaw osteonecrosis (BRONJ). With no established gold standard for BRONJ treatment, our focus is on symptom severity reduction. We aimed to assess the preventive effects of bioactive glass and/or pericardial membrane in a preclinical BRONJ model, evaluating their potential to prevent osteonecrosis and bone loss posttooth extractions in zoledronic acid (ZA)-treated animals.Methods: Rats, receiving ZA or saline biweekly for four weeks, underwent 1st and 2nd lower left molar extractions. Pericardial membrane alone or with F18 bioglass was applied post-extractions. Microarchitecture analysis and bone loss assessment utilized computerized microtomography (CT) and positron emission tomography (PET) with 18F-FDG and 18F-NaF tracers. Histological analysis evaluated bone injury. Results: Exclusive alveolar bone loss occurred post-extraction in the continuous ZA group, inducing osteonecrosis, osteolysis, osteomyelitis, and abscess formation. Concurrent pericardial membrane with F18 bioglass application prevented these outcomes. Baseline PET/CT scans showed no discernible uptake differences, but post-extraction 18F-FDG tracer imaging revealed heightened glucose metabolism at the extraction site in the ZA-treated group with membrane, contrasting the control group. Conclusion: These findings suggest pericardial membrane with F18 bioglass effectively prevents BRONJ in the preclinical model. Translational Potential of this Article: The imperative for novel therapeutic strategies aimed at facilitating alveolar bone repair remains paramount in the prevention of BRONJ subsequent to tooth extraction. Our investigation underscores that the combination of pericardial membrane and bioglass exhibits promising translational potential in the prevention of BRONJ.